PENGARUH PENYIMPANAN REAGEN KERJA TERHADAP AKTIVITAS ENZIM ALANINE AMINOTRANSFERASE - Rafika Saeba Delfiana; Tiara Dini Harlita; Agus Rudi Hartono (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
The activity of the Alanine Aminotransferase (ALT) enzyme in working reagents stored at 2 – 8°C will affect results of laboratory tests. Influencing factors are temperature and storage time. The aim of research was to determine effect of storage treatment working reagents with aliquots and without aliquots for 0, 7, 14 and 21 days at temperature 4°C on ALT enzyme activity. Research used Quasi Experimental, with Randomized Group Design. Research variables, the storage treatment of the ALT working reagent and the level of ALT enzyme activity. Sample used was 2,400 mL normal ALT control serum. Examination method is enzymatic using spectrophotometer. Data analysis used univariate analysis to calculate the average enzyme levels examined 3 times and bivariate analysis to test effect of storage treatment with Independent Sample T-test. Based on the average aliquot treatment content, highest yield on day 0, namely (59.0 U/L) and lowest yield on day 21, namely (45.7 U/L). Treatment without aliquots highest yield on day 0, namely (54.6 U/L) and lowest yield on day 21, namely (51.8 U/L). Results of treatment effect test have a significant value, aliquots can be used for up to 3 weeks and without aliquots can be used for up to 4 weeks.